Interwoven Cities - Magee, Liam.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2016)
Proposing a renovation of the metaphor of the urban fabric, Interwoven Cities develops an analysis of how cities might be woven into alternative patterns, to better sustain social and ecological life.
Keywords: Environment; Regional planning; Urban planning; Administrative law; Environmental management; Sustainable development; Social policy; Sociology, Urban; Environment; Sustainable Development; Environmental Management; Social Policy; Landscape/Regional and Urban Planning; Urban Studies/Sociology.; Administrative Law; Electronic books